2005
DOI: 10.1097/01.fjc.0000159880.12067.34
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Function Improvement by Carvedilol Therapy in Advanced Heart Failure

Abstract: Carvedilol treatment in chronic heart failure (CHF) patients has been demonstrated to reduce mortality by improving cardiac systolic function and reducing left ventricular adverse remodeling. However, the effects of the drug on left ventricular (LV) filling are less studied. In this study we evaluated early and long-term diastolic cardiac modifications by an echo-Doppler method during carvedilol therapy in patients with advanced CHF and pseudonormal or restrictive filling pattern. We studied 58 patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…In our study, mitral E/A ratio was similarly reduced with carvedilol or nebivolol therapy due to reduction of mitral E wave velocity. This finding is in accordance with the results from previous studies [10,[18][19][20]22]. In contrast, Patrianakos et al [9] have reported that mitral E/A ratio was significantly decreased with nebivolol treatment in nonischemic HF patients at 12-month follow-up, but not with carvedilol therapy.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In our study, mitral E/A ratio was similarly reduced with carvedilol or nebivolol therapy due to reduction of mitral E wave velocity. This finding is in accordance with the results from previous studies [10,[18][19][20]22]. In contrast, Patrianakos et al [9] have reported that mitral E/A ratio was significantly decreased with nebivolol treatment in nonischemic HF patients at 12-month follow-up, but not with carvedilol therapy.…”
Section: Discussionsupporting
confidence: 69%
“…In HF patients with low EF, carvedilol therapy reduced mitral E velocity, E/A ratio and IVRT while it prolonged DT [18,20,22], as in our study. In contrast, mitral inflow velocities and mitral E/A ratio remained unchanged with carvedilol therapy in HF patients in previous two studies [9,10].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The guidelines recommend their use to control ventricular rate in patients with atrial fibrillation (Class I, LOE: C). However, their use in patients with sinus rhythm and controlled hypertension receives a class IIb recommendation given the scarcity of data in this setting with a limited number of small studies showing symptomatic and/or diastolic function parameters improvement with nebivolol and carvedilol [137][138][139][140]. Contrary to HFrEF where beta-blockers have shown a remarkable survival benefit, they have failed to show any effect on mortality in HFpEF patients to date.…”
Section: Diureticsmentioning
confidence: 99%
“…Metoprolol and carvedilol can attenuate LV remodeling. [163][164][165] In a double-blind, placebo-controlled study in 394 patients with persistent AF who underwent cardioversion, metoprolol CR/XL was effective in preventing relapse into atrial fibrillation or flutter. 166 …”
Section: Beta Blockersmentioning
confidence: 99%